Hambatan Interaksi Sosial Anak Usia 4–6 Tahun: Analisis Bentuk, Penyebab, dan Peran Guru di PAUD Al Ma’sumiyah Kabupaten Serang - Susi Susanti; Maulida Nur; Inten Risna (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
This study aims to analyze the forms of social interaction barriers experienced by early childhood learners and the contributing factors that influence these difficulties in PAUD Al Ma’sumiyah, Serang Regency. Social interaction is a crucial domain of early childhood development and requires systematic stimulation both at home and in school. This qualitative descriptive study involved three children identified as having social interaction barriers, one classroom teacher, and one headmaster as supporting informants. Data were collected through observation, interviews, and documentation, and analyzed through data reduction, data presentation, and conclusion drawing. The findings reveal that children experience several forms of social interaction barriers, including excessive shyness, limited verbal communication, dependency on parents, withdrawal from peers, and challenges in cooperative play. Contributing factors include parenting patterns that are overly protective, limited interactional opportunities at home, high exposure to digital devices, and learning strategies that do not optimally facilitate peer interaction. The study recommends strengthening teacher-led social stimulation, increasing interactive learning activities, and improving communication between school and parents to enhance children’s social development